2018
DOI: 10.3390/toxins10070258
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Acute and Subchronic Toxicity and Mutagenicity of Sideritis scardica Griseb. Extracts

Abstract: Sideritis scardica Griseb. has a long history of collection from the wild as a traditional remedy for respiratory and gastrointestinal complaints. It has also been investigated for its promising pharmacological activities in the central nervous system. However, its toxicological data is entirely missing. This study investigated the acute and repeated-dose oral toxicity of a S. scardica 20% (v/v) ethanol extract in Sprague Dawley rats, and mutagenicity using the Ames test. No gross pathological abnormalities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
1
0
2
Order By: Relevance
“…Regarding Sideritis, although previously found to be cytotoxic in cancer cell lines [74], our experiments did not reveal toxic effects (distress or death) in animals who received either the low or the high dose of the extract. This comes in line with two previous toxicological studies that proved the safety of S. scardica and S. Taurica [75,76].…”
Section: Availability Of Data and Materialsupporting
confidence: 91%
“…Regarding Sideritis, although previously found to be cytotoxic in cancer cell lines [74], our experiments did not reveal toxic effects (distress or death) in animals who received either the low or the high dose of the extract. This comes in line with two previous toxicological studies that proved the safety of S. scardica and S. Taurica [75,76].…”
Section: Availability Of Data and Materialsupporting
confidence: 91%
“…Pharmacological studies on different preparations of the species have shown its potential in treating Alzheimer's disease [9], as well as being an anticancer agent [11]. Moreover, studies have shown a lack of toxicity and a favorable mutagenic profile, confirming the safety of the plant, as evidenced in its wide traditional application [12].…”
Section: Introductionmentioning
confidence: 92%
“…However, the data found for an ethanolic ower extract of Chamomile recutita (synonym of Matricaria chamomile) demonstrated a high safety margin, as the animals tolerated up to 10,000 mg kg body weight of the extract orally in the acute toxicity study and tolerated repeated doses of up to 500 mg kg for 28 days [18]. Regarding Sideritis angustifolia (cat's tail), no animal toxicity studies were found; however, the Sideritis scardica ethanol extract was not toxic after administration of a single dose of 2000 mg/kg bw and repeated doses of 1000 mg/kg bw for 28 days [19]. From the data obtained in our experiments and those reviewed in the literature, we can conclude that these species have a high safety pro le and the dose we used for the intestinal motility assay (300 mg/kg bw) is well below LD50.…”
Section: Acute and Subacute Toxicitymentioning
confidence: 99%